A Configurable Smart E-Nose for Spatio-Temporal Olfactory Analysis - Sánchez-Garrido, José Carlos; González-Monroy, Javier; González-Jiménez, Antonio Javier (My University, 2014)
This paper describes a novel electronic nose (enose) aimed at applications that require knowing not only the gas composition and concentration, but also its temporal and spatial evolution. This is done by capturing additional information related to the chemical substance such as the timestamp and geo-location of the measurements, as well as other physical magnitudes of the environment like temperature and humidity for correcting and interpreting the data. The device has been conceived following a modular architecture as a set of independent smart modules, which are interconnected and controlled through an I2C interface by a central processing unit. Each smart module can identify itself, store settings for autoconfiguration and perform signal pre-processing of the measured variables. Smart module types include: chemical sensors, communication interfaces, batteries, data storage, GPS, temperature and humidity.
Keywords: Ruido electrónico; Olfaction; Electronic noise